1996
DOI: 10.1152/jappl.1996.81.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Myonuclear number and myosin heavy chain expression in rat soleus single muscle fibers after spaceflight

Abstract: The effects of 14 days of spaceflight on myonuclear number, fiber size, and myosin heavy chain (MHC) expression in isolated rat soleus muscle fiber segments were studied. Single soleus muscle fibers from rats flown on the Spacelab Life Sciences-2 14-day mission were compared with those from age-matched ground-based control rats by using confocal microscopy and gel electrophoresis. Spaceflight resulted in a significant reduction in the number of fibers expressing type I MHC and an increase in the number of fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
168
3
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(203 citation statements)
references
References 0 publications
25
168
3
7
Order By: Relevance
“…5) [76]. The results indicated that the percent distribution of fibers which expressed only slow MHC apparently decreased, and some of the slow fibers began to co-express some fast MHC as well.…”
Section: Fiber Phenotypementioning
confidence: 93%
“…5) [76]. The results indicated that the percent distribution of fibers which expressed only slow MHC apparently decreased, and some of the slow fibers began to co-express some fast MHC as well.…”
Section: Fiber Phenotypementioning
confidence: 93%
“…It is generally accepted that muscle hypertrophy is related to an increased myonuclear number through activation of satellite cells (Kadi et al, 2005;Mackey et al, 2007), while muscular atrophy is related to an apoptotic decrease in myonuclear number (Allen et al, 1997a,b;Alway & Siu, 2008). However, there are several reports demonstrating a less stringent relationship between myonuclear number and fibre size, i.e., there are reports of muscle fibre hypertrophy without satellite cell activation (McCarthy & Esser, 2007) as well as atrophy accompanied by either an increased, decreased or unaltered number of myonuclei (Allen et al, 1995(Allen et al, , 1996(Allen et al, , 1997aKasper & Xun, 1996;Gundersen & Bruusgaard, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The muscle fiber type is known to change during atrophy according to the causes that trigger the atrophy. For example, disuse muscular atrophy that arises according to the fixed-joint or dangling hind-leg model exhibits a decrease in type I fibers and an increase in type II fibers 34,35) . MyoD and HMGCoA-reductase inhibition have been suggested to participate in myosin 36,37) .…”
Section: Changes In Muscle Type During Atrophymentioning
confidence: 99%